The ancient magus' bride. Volume 8 - Yamazaki, Kore; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2018)
Chise may have stopped the dragon's rampage, but at a great cost: she has been cursed, and a dragon's curse is unbreakable! Chise and Elias are visited by Marielle the witch, whose fellow witches claim to know the secret to helping Chise. There's one catch -- in exchange for their aid, Chise must join the witches' coven.